Efek Proteksi Fraksi Etil Asetat Daun Surian (Toona sureni (Blume) Merr. ) terhadap Aterosklerosis - Suhatri Suhatri; Netty Marusin; Delva Yeni; Rahmi Yosmar (Fakultas Farmasi Universitas Andalas, 2014)
A study of the protection effect of ethyl acetate fraction of toona leaves (Toona sureni (Blume) Merr.) to the atherosclerotic blood vessel on the hypercholesterolemic quails has been carried out. The observation was conducted for histopathology of the blood vessel. The hypercholesterolemic quails were obtained through high-fat diet and propylthiouracil (PTU) induction. Aortic wall thickness, changes on the aortic lumen are, and visual endothelial cell dysfunction were determined. The study showed that the ethyl acetate fraction of toona leaves on the dose of 50 mg/kg body weight exhibited the best protection effect, indicated by aortic wall thickness and lumen area, and the degree of endothelial cell dysfunction which were not significantly different with the negative control group (p>0.05), but significantly different with positive control group (p<0.05).